2017
DOI: 10.1089/ars.2016.6795
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor (Erythroid-Derived 2)-Like 2 and Thioredoxin-1 in Atherosclerosis and Ischemia/Reperfusion Injury in the Heart

Abstract: Therefore, the length of treatment with Nrf2 activators and/or Trx-1 has first to be studied in more detail in cardiovascular disorders. Moreover, a combination of Nrf2 activators and Trx-1 should be investigated and taken into consideration. Antioxid. Redox Signal. 26, 630-644.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 117 publications
(108 reference statements)
2
37
0
Order By: Relevance
“…The observed increase in the NQO1 gene expression in our study might be a response to NRF2-stimulating conditions prevalent in patients with CKD, like oxidative stress or lipopolysaccharide-induced inflammation [25, 26]. Patients with coexisting CVD, which is also associated with oxidative stress, might be especially affected [27]. This is supported by the higher CVD prevalence in CKD 1–5 patients with a higher NQO1 gene expression that we observed.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The observed increase in the NQO1 gene expression in our study might be a response to NRF2-stimulating conditions prevalent in patients with CKD, like oxidative stress or lipopolysaccharide-induced inflammation [25, 26]. Patients with coexisting CVD, which is also associated with oxidative stress, might be especially affected [27]. This is supported by the higher CVD prevalence in CKD 1–5 patients with a higher NQO1 gene expression that we observed.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, as the systemic application of NRF2 activators affects different cell and tissue types, the NRF2 pathway in kidney disease needs to be investigated in different human cells and tissues. This is of relevance as the overactivation of a potent transcription factor like NRF2 was suggested as potentially deleterious for the cardiovascular system [27]. Therefore, a preexisting activation of the NRF2 system in CKD patients especially with CVD, as suggested by our results, could be seen in line with the increased rate of cardiovascular events in the BEACON trial [11].…”
Section: Discussionsupporting
confidence: 67%
“…In MIRI, Nrf2 downregulates the inflammatory factor myeloperoxidase (MPO) and simultaneously upregulates the levels of antioxidants, such as SOD and glutathione peroxidase (GPx), to counter inflammation and oxidative stress. Jakobs et al demonstrated that Nrf2 is maintained in the reduced state to increase the expression of antioxidative enzymes by thioredoxin-1 (Trx-1), and in turn, Nrf2 regulates the activation of Trx-1 through two AREs [45]. As demonstrated by Chen et al, Nrf2 is able to not only function after inflammation and oxidative stress but also after reperfusion injury, via activation by trigger factors such as emulsified isoflurane (EI) [46].…”
Section: Myocardial Ischemia Reperfusion Injury (Miri)mentioning
confidence: 99%
“…Regulates the activation of thioredoxin-1 (Trx-1) through two antioxidant response elements [45] Regulates ROS levels [46] Atherosclerosis (AS)…”
Section: Viral Myocarditismentioning
confidence: 99%
“…Besides the proteins involved in the lipid metabolism (apolipoproteins and their receptors, PCSK9, paraoxonases, etc. ), several main classes of biomolecules also play an important role in the pathogenesis of atheroma formation: scavenger receptors [3][4][5][6]; growth factors and other cytokines and chemokines [7][8][9][10][11][12][13][14]; adhesive moleculesintegrins, cadherins, selectins and immunoglobulins [15][16][17][18]; matrix metalloproteinases [19][20][21]; nitric oxide (NO) and endothelial NO synthase [22][23][24]; free radicals, oxidative stress and antioxidant systems [23][24][25][26][27]; transcription factors [28][29][30][31]. Atherogenesis is a complex process driven by interactions between environmental and genetic factors and their discovery and validation in individuals with different population background could impact on the prevention and risk estimation of CHD.…”
Section: Introductionmentioning
confidence: 99%